Dari Psikologi Kritis dan Psikologi Kultural-historis ke Psikologi Berhampiran Budaya - Augustinus Supratiknya (Sanata Dharma University, 2023)
Critical psychology and cultural-historical psychology are two approaches emerging as critiques to mainstream psychology that is often perceived to be hedonistic and individualistic. Adopting the spirit of critical psychology and cultural-historical psychology that strive to break the grips of mainstream psychology as well as absorbing the inspiration from Thomas Teo’s psychological humanities, Svend Brinkmann’s cultural psychology, Richard Johnson’s cultural circuit, and Stuart Hall’s cultural studies, as a critical review this article proposes an approach coined as psikologi berhampiran budaya (culturally-turned psychology) based on the socio-cultural realities of the present-day Indonesian society. Psikologi berhampiran budaya offers four models of psychological research in the production of knowledge on both the subject and the society of the present-day Indonesia. The application of the four models in such culturally turned production of knowledge is expected to simultaneously and serendipitously produce a specifically Indonesian psychology.